2020
DOI: 10.3390/molecules25184262
|View full text |Cite
|
Sign up to set email alerts
|

Structural Heterogeneities of the Ribosome: New Frontiers and Opportunities for Cryo-EM

Abstract: The extent of ribosomal heterogeneity has caught increasing interest over the past few years, as recent studies have highlighted the presence of structural variations of the ribosome. More precisely, the heterogeneity of the ribosome covers multiple scales, including the dynamical aspects of ribosomal motion at the single particle level, specialization at the cellular and subcellular scale, or evolutionary differences across species. Upon solving the ribosome atomic structure at medium to high resolution, cryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 141 publications
(158 reference statements)
1
15
0
Order By: Relevance
“…During the embryonic period in birds, rapid morphogenesis, differentiation, and development of various organs require support from cell division, consisting of quick connection of gene expression programs, acceleration of the translation programs, and quick regulation of protein synthesis ( Guo, 2018 ). During the process, the control of translation is considered the main determining factor of the protein level in the cell, while the ribosome, as the translation machine in protein synthesis plays a central role in the regulation of gene expression ( Bowman, et al, 2020 ; Javed and Orlova, 2019 ; Natchiar, et al, 2015 ; Poitevin, et al, 2020 ). Ribosome and translational control are directly linked with stem cell homeostasis and control of cell fate and play vital roles in the translational regulatory network that controls the identity of stem cells ( Gabut, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the embryonic period in birds, rapid morphogenesis, differentiation, and development of various organs require support from cell division, consisting of quick connection of gene expression programs, acceleration of the translation programs, and quick regulation of protein synthesis ( Guo, 2018 ). During the process, the control of translation is considered the main determining factor of the protein level in the cell, while the ribosome, as the translation machine in protein synthesis plays a central role in the regulation of gene expression ( Bowman, et al, 2020 ; Javed and Orlova, 2019 ; Natchiar, et al, 2015 ; Poitevin, et al, 2020 ). Ribosome and translational control are directly linked with stem cell homeostasis and control of cell fate and play vital roles in the translational regulatory network that controls the identity of stem cells ( Gabut, et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of even more advanced algorithms and software ( Kimanius et al, 2021 ), together with the refinement of the technique itself to achieve higher resolution ( Pellegrino et al, 2022 ), will provide fundamental information on all the ribosomal modifications and detailed interactions in the three-dimensional structure of the native human ribosome. Although some limitations still exist due to the low throughput and time-consuming techniques, cryo-EM will be extremely useful to recognize how particular molecules can bind to specific modified sites in ribosomes and inhibit their activity, offering new insights for structure-based drug design ( Gilles et al, 2020 ; Poitevin et al, 2020 ).…”
Section: Pseudouridylation Detection Methodsmentioning
confidence: 99%
“…To analyze these complex dynamics, molecular dynamics simulations were previously used [18] to study how the dynamics of the nascent chain are impacted by various biophysical properties of the tunnel, including its geometry [7,[19][20][21], electrostatics [5,22] and 1 hydrophobicity [23]. With the increasing availability of high-resolution structures of the ribosome for various species [24], detailed mappings of the exit tunnel have revealed that these properties can vary across the domains of life [15,19]. Most notable are the geometric differences in tunnel lengths and diameters, as eukaryotic tunnels are, on average, shorter and substantially narrower than prokaryote ones.…”
Section: Introductionmentioning
confidence: 99%